Influence of growing environment on growth, yield and chemical composition of strawberry (Fragaria x ananassa) fruits under open vs naturally ventilated polyhouse conditions - SWAPNIL PANDEY; JEETENDRA SINGH; SANJAY KUMAR SINGH; I B MOURYA (The Indian Journal of Agricultural Sciences, 2015)
Strawberry (Fragaria x ananassa Duch.) is grown extensively in the plastic greenhouses for higher productivity and off season production. The growing environment influences morphology, composition and quality of strawberry fruits. A study was conducted to determine the effects of growing environment on various growth, yield and fruit quality parameters of Winter Dawn strawberry under semi-arid conditions of Rajasthan. The results reveal that the fruits harvested from the open field condition had higher root volume, root weight, number of roots/plant and total chlorophyll content (2.02 mg/g), maximum leaves/plant (73.33), fruit length and fruit weight. In naturally ventilated polyhouse, strawberry plants had higher crown height, plant spread and produced higher fruit yield (242.77 g/plant) with maximum number of fruits/plant (29.00) and total anthocyanin content (45.51 mg per 100 g) in the fruits. In contrast, fruits of open field conditions have recorded higher total and reducing sugar content, vitamin C content (50.32 mg per 100 g) and maximum sensory scores (8.35 out of 10) which indicates that both types of environmental conditions are favourable for strawberry.